RESIDUAL RENAL VOLUME IS ASSOCIATED WITH VOLUME STATUS DETERMINED BY BODY COMPOSITION MONITORING IN PATIENTS WITH PERITONEAL DIALYSIS - Jae Hyun Chang; Han Ro; Ji Yong Jung; Hyun Hee Lee; Wookyung Chung (The Korean Society of Nephrology, 2012)
Fluid overload has been linked to mortality in peritoneal dialysis (PD) patients. Residual renal function is important for patient survival. Therefore, the objective of this study was to analyze volume status in PD patients, and to identify associations between volume status and residual renal volume. We performed a cross-sectional, observational, single-center study. Body composition was measured using a portable multifrequency whole-body bioimpedance assessment, and residual renal volume was measured. We examined 75 patients (66.7% male), with a mean age of 50.7±13.0 years and mean body mass index of 23.5±3.5 kg/m2. Length of time on dialysis was 46.5±37.9 months. Anuria (≤100 mL/day) is associated with relative overhydration (ROH) (p=0.014) and extracellular water volume (p=0.014). In a multivariable linear regression analysis, anuria (coefficient β=0.217, p=0.025), diabetes (coefficient β=0.213, p=0.027), and serum albumin level (coefficient β=−0.533, p<0.001) were independent significant parameters associated with ROH. In conclusion, residual renal volume is negatively associated with overhydration in PD patients. We suggest that preservation of residual renal volume is important to maintain volume status in PD patients.